Midwifery Care and Family Social Support for Pregnant Women with Mild Anemia in the Third Trimester (Journal of Social And Education Research, 2025)
Anemia during pregnancy is a significant health issue in developing countries, contributing to high maternal and fetal morbidity and mortality rates. This study focuses on severe anemia among pregnant women in their third trimester, examining prevalence, causes, and effective interventions. The findings indicate that limited knowledge about anemia and poor adherence to iron supplementation are key factors leading to anemia in pregnancy. Data from clinical visits showed that educational interventions aimed at increasing awareness, combined with iron tablet supplementation, significantly improved hemoglobin levels and maternal health. Hemoglobin levels in participants increased from severe anemia levels (<9 g/dL) to near-normal ranges after intervention. The study also highlights the role of family support and consistent antenatal care in managing anemia effectively. Nutritional education addressing iron-rich diets and the avoidance of substances inhibiting iron absorption proved essential. These results align with prior research emphasizing education and supplementation as critical strategies to reduce anemia-related pregnancy complications such as miscarriage, preterm birth, and low birth weight. The study recommends strengthening antenatal care programs by integrating comprehensive nutritional education and monitoring to ensure compliance with iron supplementation. Improving pregnant women’s and their families’ knowledge on anemia prevention is crucial to reducing maternal and fetal risks associated with anemia. This approach can ultimately contribute to better pregnancy outcomes and reduced maternal mortality rates.